2018
DOI: 10.1111/jpi.12473
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuated retinal neovascularization and neuroglial dysfunction by inhibition of HIF‐1α‐VEGF pathway in oxygen‐induced retinopathy mice

Abstract: Retinopathy of prematurity (ROP) is a retinopathy characterized by retinal neovascularization (RNV) occurring in preterm infants treated with high concentrations of oxygen and may lead to blindness in severe cases. Currently, anti-VEGF therapy is a major treatment for ROP, but it is costly and may cause serious complications. The previous study has demonstrated that melatonin exerted neuroprotective effect against retinal ganglion cell death induced by hypoxia in neonatal rats. However, whether melatonin is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 66 publications
(159 reference statements)
6
69
1
Order By: Relevance
“…All animal studies were approved by the Institutional Animal Care and Use Committee of Zhongshan Ophthalmic Center and adherence to the ARVO Animal Statement. Oxygen‐induced retinopathy (OIR) was generated as previously described . Neonatal mice and their nursing mother were exposed to 75% oxygen from P7‐12 to induce retinopathy, and the mice were killed at P17.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All animal studies were approved by the Institutional Animal Care and Use Committee of Zhongshan Ophthalmic Center and adherence to the ARVO Animal Statement. Oxygen‐induced retinopathy (OIR) was generated as previously described . Neonatal mice and their nursing mother were exposed to 75% oxygen from P7‐12 to induce retinopathy, and the mice were killed at P17.…”
Section: Methodsmentioning
confidence: 99%
“…Oxygeninduced retinopathy (OIR) was generated as previously described. 21 Neonatal mice and their nursing mother were exposed to 75% oxygen from P7-12 to induce retinopathy, and the mice were killed at P17. The retinas of the neonatal mice were collected, and the total RNA including miRNA of the entire retinas was extracted using the miRNeasy Mini kit (Qiagen, Hilden, Germany).…”
Section: Oxygen-induced Retinopathy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser photocoagulation, the standard treatment for proliferative retinopathy, has a high rate of visual and anatomic success (Wallace and Wu, 2013). Anti-VEGF drugs are widely used as the major treatment in both ROP and DR to achieve certain efficacy (Xu et al, 2018). However, despite these considerable advances, an increasing number of clinical studies have reported that laser treatment and anti-VEGF therapy does have some limitations and causes undesirable side effects (Potente et al, 2011;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-VEGF drugs are widely used as the major treatment in both ROP and DR to achieve certain efficacy (Xu et al, 2018). However, despite these considerable advances, an increasing number of clinical studies have reported that laser treatment and anti-VEGF therapy does have some limitations and causes undesirable side effects (Potente et al, 2011;Xu et al, 2018). Therefore, it is critical to explore and identify additional factors that regulate pathological neovascularization in order to exploit new therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%